EXPLORING KAZAKHSTANI PRIMARY TEACHERS’ VALUES AND BELIEFS OF MOBILE-ASSISTED LANGUAGE LEARNING (MALL) - Niyazbayeva, Venera (Graduate School of Education, 2023)
Mobile-assisted Language learning is gaining popularity among language teachers worldwide (Chen & Tsay, 2021; Cavus & Ibrahim, 2017; Ernawati, 2019). Kazakhstan's trilingual policy and its focus on international cooperation have resulted in education modernization and digitalization, promoted new language education methodologies, and using Information and Communication Technologies (ICT) to be globally competitive (SPESD, 2019; Smagulova, 2016; Zhetpisbayeva, 2016). There are emerging Kazakhstani MALL studies in higher education focusing on students' learning and attitudes with no or limited research about MALL pedagogy (Cig et al., 2017; Krivoruchko et al., 2015; Torekeyev & Shadkam, 2019). Another gap in the Kazakhstani literature is MALL implementation in schools, which this qualitative case study addresses by exploring primary Kazakh as a second language (KL2) and English as a foreign language (EFL) teachers' MALL beliefs and practices. To ensure the validity and reliability of my research findings, I employed methodological triangulation by combining multiple research methods, including questionnaires on the multimodal platform “Menti”, images, and interviews. Using the Mobile Technology Pedagogy and Content Knowledge (MTPACK) analytical model, this study has demonstrated that the value of MALL for teachers lies in their constructivist beliefs, including promoting active and interactive learning in KL2 and EFL, enhancing student motivation and engagement, and serving as a useful tool for assessing and accommodating student diversity and unique learning styles. The study contributes to the MALL literature in the Kazakhstani context and concludes that MALL professional development programs are needed to support teachers in effectively incorporating them into their teaching practices. Finally, the MTPACK framework provided a useful lens for analyzing MALL practices and understanding the role of technology in language teaching in the Kazakhstani context.
Keywords: Type of access: Open Access; Mobile Learning; language learning; mobile pedagogy; MALL; TPACK; Social Constructivism; Kazakh language; KL2; English language; EFL